2007
DOI: 10.1073/pnas.0706568104
|View full text |Cite
|
Sign up to set email alerts
|

Circuit theory predicts gene flow in plant and animal populations

Abstract: Maintaining connectivity for broad-scale ecological processes like dispersal and gene flow is essential for conserving endangered species in fragmented landscapes. However, determining which habitats should be set aside to promote connectivity has been difficult because existing models cannot incorporate effects of multiple pathways linking populations. Here, we test an ecological connectivity model that overcomes this obstacle by borrowing from electrical circuit theory. The model vastly improves gene flow pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
730
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 813 publications
(745 citation statements)
references
References 29 publications
10
730
0
5
Order By: Relevance
“…Landscape surfaces were coded such that each pixel was assigned a value representing resistance to gene flow. Subsequently, we used the gdistance package in R to quantify pairwise resistance between two groups as the expected correlate to the amount of gene flow between two groups (i.e., higher pairwise resistance equates to lower expected movement; McRae, 2006; McRae & Beier, 2007). Pairwise effective resistance values are a function of the flow of current—representative of gene flow—and therefore incorporate geographic distance (McRae & Beier, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Landscape surfaces were coded such that each pixel was assigned a value representing resistance to gene flow. Subsequently, we used the gdistance package in R to quantify pairwise resistance between two groups as the expected correlate to the amount of gene flow between two groups (i.e., higher pairwise resistance equates to lower expected movement; McRae, 2006; McRae & Beier, 2007). Pairwise effective resistance values are a function of the flow of current—representative of gene flow—and therefore incorporate geographic distance (McRae & Beier, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…All raster surfaces were resampled using bilinear interpolation to a resolution of 1.2 km. Overall, changes in resolution should not have a strong effect on pairwise resistance values (McRae & Beier, 2007; Row et al., 2015). In all cases, we compare results to resistances derived from an undifferentiated landscape in which all cells had a resistance of one.…”
Section: Methodsmentioning
confidence: 99%
“…CIRCUITSCAPE incorporates circuit theory to quantify the total landscape resistance between individuals via multiple potential paths of least resistance (McRae & Beier, 2007). We used Mantel (Mantel, 1967) and partial Mantel tests (Smouse, Long, & Sokal, 1986) to correlate genetic and geographic/resistance distances.…”
Section: Methodsmentioning
confidence: 99%
“…This approach takes into account the effect of all alternative pathways between habitat patches, which is especially appropriate when the specific aim is to assess gene flow across a landscape over many generations. Several studies indicated that resistance distances may allow for better assessment of genetic isolation-by-distance than the usual Euclidean or least-cost-path distance because the metric is based on assumptions about the impact of many alternative routes in the entire landscape on the dispersal of individuals, and consequently on the chances of gene flow (McRae and Beier 2007;Schwartz et al 2009;Lozier et al 2013). Despite the theoretical superiority of isolation-by-resistance approach over distance measures assuming a single optimal path, the performance of the these approaches have rarely been evaluated with empirical data sets at finer spatial scales (Row et al 2010).…”
Section: Introductionmentioning
confidence: 99%